Hyperamylasaemia and 6 hours post ERCP pancreatitis among patients attending Hospital Raja Perempuan Zainab II (HRPZ II) - Mat, Ann Dasimakamalia (2021)
Background: Pancreatitis remains a major complication of endoscopic retrograde cholangiopancreatography (ERCP) with a prevalence of 2%-9%.Young age, female gender, difficulty in bile duct cannulation, pancreatic sphincterotomy, and sphincter of Oddi dysfunction have been found to be risk factors. Serum amylase and lipase levels are regarded as useful markers for early diagnosis of pancreatitis. However timing of amylase level taken after ERCP is not standardised among different centres. This study is to determine association of post ERCP pancreatitis with 6-hour amylase level after ERCP. Methods: This is a retrospective review of patients undergoing ERCP in Hospital Raja Perempuan Zainab II from 1st January 2015 to 31st December 2018. Serum amylase level at 6-hour after ERCP and complications after ERCP were reviewed. The association of amylase level 6-hour after ERCP and pancreatitis was determined. Results: A total of 308 patients were included in this study of which 41 (13.3%) had post ERCP pancreatitis. Amylase level of more than 300IU at 6-hour after ERCP (p < 0.001) and sphincterotomy (p=0.028) associated with post ERCP pancreatitis. Conclusion: Post ERCP pancreatitis is associated with an increase in serum amylase level greater than 300IU at 6-hour after ERCP.